METHODOLOGY OF USING DIFFERENT SOCIAL FORMS IN FOREIGN LANGUAGE CLASSES (American Journal of Business Management, Economics and Banking, 2022)
This article discusses the methodology of using different social forms in foreign language classes, in particular, individual work, pair work, small group work, frontal work, team work.